Defect prediction model for testing phase - Mohamed Suffian, Muhammad Dhiauddin (2009)
The need for predicting defects in testing phase is important nowadays as part of the improvement initiatives for software production process. Being the group that ensuring successful implementation of verification and validation process area, all test engineers in Test Centre of Excellence (Test COE) department are required to play their part to discover software defects as many as possible and contain them within testing phase. This research is aimed to achieve zero-known post release defects of the software delivered to end-user. To achieve the target, the research effort focuses on establishing a defect prediction model for testing phase using Six Sigma methodology. It identifies the customer needs on the requirement for the prediction model as well as how the model can benefits them. It also outlines the possible factors that associated to defect discovery in testing phase. Analysis of the repeatability and capability of test engineers in finding defects are elaborated. This research also describes the process of identifying type of data to be collected and techniques of obtaining them. Relationship of customer needs with the technical requirements is then explained clearly. Finally, the proposed defect prediction model for testing phase is demonstrated via regression analysis. This is achieved by considering faults found in phases prior to testing phase and also the code size of the software. The achievement of the whole research effort is described at the end of this project together with challenges faced and recommendation for next research work.